PENERAPAN PRINSIP TRANSPARANSI DI LINGKUNGAN PERADILAN TINGKAT PERTAMA DI YOGYAKARTA - Ishviati J Koenti (Universitas Janabadra, 2018)
Transparency is the principle to open up to the right of the people to obtain correct, honest and non-discriminatory information about governance. Transparency has an important position in implementing